Tinjauan Self-Efficacy Siswa pada Model Pembelajaran Missouri Mathematics Project terhadap Kemampuan Komunikasi Matematis - Asfanudin, Imam Nurrochman; Kurniawati, Ira; Riki Andriatna (SJME (Supremum Journal of Mathematics Education), 2024)
This study aims to see the effect of Missouri Mathematics Project learning model on students' mathematical communication ability in terms of students' mathematical self-efficacy. This research is a quasi-experimental. The population in this study were all grade X students in one of the public high schools in Surakarta city in 2023. The sample in this study was taken by cluster random sampling consisting of two classes, namely the experimental class that received the Missouri Mathematics Project learning model and the control class that received the Problem-Based Learning model. Data collection techniques through questionnaires to obtain data on student self-efficacy and student mathematical communication ability tests to obtain data on students' mathematical communication ability. Data analysis technique used two-way ANOVA with unequal cells. The results showed that the mathematical communication ability of students who were given the Missouri Mathematics Project learning model were better than students who were given the Problem-Based Learning model, both in general and in terms of student self-efficacy, both high, medium, and low. In the aspect of self-efficacy, both in general and in each learning model, high self-efficacy has the same good mathematical communication ability as moderate self-efficacy, high self-efficacy students have better mathematical communication ability than students with low self-efficacy, and moderate self-efficacy students have better mathematical communication ability.